Electrochemical CO2 reduction by a cobalt bipyricorrole complex: decrease of an overpotential value derived from monoanionic ligand character of the porphyrinoid species. Issue 4 (14th December 2018) - Ogawa, Ayumu; Oohora, Koji; Gu, Wenting; Hayashi, Takashi
Abstract : Bipyricorrole serves as a useful monoanionic ligand in a Co-based catalyst for a selective CO2 -to-CO reduction with low overpotential. Abstract : A newly synthesized Co(ii ) complex with a monoanionic bipyricorrole ligand is found to catalytically promote a selective CO2 electroreduction to CO with Faradaic efficiency of 75%. Catalytic Tafel plots show that the overpotential of Co(ii ) bipyricorrole is 0.35 V lower than that of a Co(ii ) complex with the dianionic tetraphenylporphyrin ligand.